1998
DOI: 10.1021/ed075p206
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Perception Skills of Chemistry Students

Abstract: General chemistry students in four different courses spanning a 12-year period were given a paper-pencil reasoning test entitled An Inventory of Piagetian Developmental Tasks (IPDT). A subset of twelve questions from this test, representing visualization abilities, were used to investigate spatial perceptual skills of students with regards to gender and course level. These findings indicate statistically significant differences in test scores based on gender, showing that males scored higher than females. A lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 8 publications
0
45
1
8
Order By: Relevance
“…Traditionally, many researchers have cited a student's inability to visualize the three-dimensional structure embedded in two-dimensional representations as the primary barrier to learning. Although some have suggested that the barrier results from the total amount of information that each particular representation contains (Keig & Rubba, 1993;Kozma et al, 2000;Stieff & Wilensky, 2003), most researchers have repeatedly emphasized that it is the spatial information, in particular, embedded within each representation that confuses students (Bodner & Guay, 1997;Brownlow & Miderski, 2001;Carter, LaRussa, & Bodner, 1987;Coleman & Gotch, 1998). The latter group of researchers emphasizes that the threedimensional structure of a molecule plays a large role in the molecule's properties and reactivity, and they suggest that students must stay mindful of these features in order to understand and complete most chemistry tasks.…”
Section: Principle 2: Investigate the Role And Efficacy Of Visualizatmentioning
confidence: 99%
“…Traditionally, many researchers have cited a student's inability to visualize the three-dimensional structure embedded in two-dimensional representations as the primary barrier to learning. Although some have suggested that the barrier results from the total amount of information that each particular representation contains (Keig & Rubba, 1993;Kozma et al, 2000;Stieff & Wilensky, 2003), most researchers have repeatedly emphasized that it is the spatial information, in particular, embedded within each representation that confuses students (Bodner & Guay, 1997;Brownlow & Miderski, 2001;Carter, LaRussa, & Bodner, 1987;Coleman & Gotch, 1998). The latter group of researchers emphasizes that the threedimensional structure of a molecule plays a large role in the molecule's properties and reactivity, and they suggest that students must stay mindful of these features in order to understand and complete most chemistry tasks.…”
Section: Principle 2: Investigate the Role And Efficacy Of Visualizatmentioning
confidence: 99%
“…The ability to seamlessly transition between physical models and mental models is important to student success. This ability is most commonly referred to as spatial ability or reasoning (Coleman & Gotch, 1998;Harle & Towns, 2011;Suits & Sanger, 2013).…”
mentioning
confidence: 99%
“…(Sawyer, 2014, p. 5) www.crossingtheborder.com.np ese points highlight the important role of the spatial in authentic situated practice, particularly in STEM subjects. Furthermore, several studies have already established the correlation between spatial skills and success in a variety of STEM disciplines (Hegarty et al, 2010) such as chemistry (Coleman & Gotch, 1998), engineering (Peters, Chisholm, & Laeng, 1995;Sorby, 2001), geology (Orion, Ben-Chaim, & Kali, 1997), mathematics (Casey, Nuttall, & Pezaris, 1997), physics (Kozhevnikov, Motes, & Hegarty, 2007) and medicine (Keehner et al, 2004;Schueneman, Pickleman, Hesslein, & Freeark, 1984), so spatial thinking is relevant in preparing students for careers in these elds.…”
Section: Spatial Thinking and Learning As Interdisciplinarymentioning
confidence: 99%